Stalag Luft III : an official history of the "Great Escape" PoW camp : an official account - Tuck, Howard (2016)
Zusammenfassung: "This Official History of the camp was prepared for the War Office but was never released to the general public. It explains the German administration and running of the camp, the food and conditions the prisoners endured, and the means by which morale was maintained under such trying circumstances. Inevitably considerable space is devoted to the escapes and their careful preparation as well as the anti-escape measures undertaken by the guards. There is also a chapter detailing the punishments meted out for attempting to escape, and lists the number of shooting incidents. This account provides the reader with an accurate and unprecedented insight into life in a German PoW camp in the latter years of the Second World War." - publisher